A Hybrid Fuzzy Logic FOPID Position Controller for DC Motor Driving Tracking Systems System - Mohamed M. Ismail; Ahmed F. Elbendary; Abdelghany M. Abdelghany (Institute of Advanced Engineering and Science, 2017)
This paper presents a developed application for using Fraction Order PID controller (FOPID) in controlling of DC motors installed incelestron telescope, this is done through controlling the angles of two DC motors driven the telescope. The model of celestron telescope is mathematically represented by highly non linear differential equations, this types of nonlinear model is recommended to be controlled using Artificial Intelligent based controller. In this paper, optimal fuzzy FOPID is implemented instead of conventional PID controllers. Genetic Algorithm, fuzzy logic are used for tuning the FOPID parameters.FOPID controller is based on position error and its rate of change as an input vector, the proposed controller set presents a complete precision in forcing the telescope motors to satisfy the predefined position. The simulation results show the dynamic response of the system and the enhancement achieved in rising time and settling time when using FOPID. The response of FOPID is compared with the conventional PID with the same input position reference.